Myths of Primitiveness: A Barthean Interpretation of Rhetorical Devices in Early Jazz Criticism - Alonso Recarte, Claudia (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2013)
Ever since jazz began to make an impact in white aesthetic culture in the late 1910s and 1920s, critics, regardless of whether they celebrated or condemned the music, enmeshed their discourse with images of exoticism, noble savageness, and racial brutishness. As Jazz Studies emerged as an academic discipline, scholars have shown increasing interest in exposing these images in order to illustrate the pervading racist sentiment inscribed within white perception of the jazz idiom and also to establish the connections between jazz and the modernist obsession with primitivism. The aim of this paper is to contribute further study to the intricacies of primitivism through a close examination of the rhetorical devices enabling the subsistence and efficiency of the white supremacy’s mystification of jazz. In this way, we may better comprehend how the primitivist construct is not a matter of an ideology’s conglomeration of superficial images, nor of mere associations between the music and rituals. These features are certainly operative, but by approaching the metaliguistic techniques implicit in what Roland Barthes calls the bourgeois myth, jazz primitiveness can be conceived as an act of colonization that begins and is self-nurtured by patterns of speech.